Reliability and Validity of a Breastfeeding Attitudes Instrument for Nursing Staff - Dávila-Torres, René R.; Parrilla, Ana M.; Gorrín-Peralta, José (Puerto Rico Health Sciences Journal, 2013)
See manuscript